THE EFFECT OF TWO METHODS OF NIGELLA OIL EXTRACTION ON CHEMICAL COMPOSITION - Hussein, El-Sayed H.; Hassan, M.R. (Emirates Journal of Food and Agriculture, 2017)
Please see the scanned pdf version in full text